Immunological Adverse Events After Autologous Hematopoietic Stem Cell Transplantation in Systemic Sclerosis Patients - Patrick-Pascal Strunz; Matthias Froehlich; Michael Gernert; Eva Christina Schwaneck; Anna Fleischer; Ann-Christin Pecher; Hans-Peter Tony; Joerg Christoph Henes; Marc Schmalzing (Frontiers in Immunology, 2021)
Autologous hematopoietic stem cell transplantation (aHSCT) represents an effective treatment for systemic sclerosis (SSc), but it also can cause immunological adverse events (iAEs). Therefore, we aimed to determine the frequency of iAEs [engraftment syndrome (ES) and secondary autoimmune disorder (sAD)] and to identify potential risk factors for their development in a retrospective analysis on 22 patients similarly transplanted due to SSc. While nine patients (41%) suffered from ESs, seven sADs occurred in six patients (27%). Patients who developed ES were older in our cohort (52.45 vs. 42.58 years, p = .0433, Cohen’s d = 0.86), and cardiac involvement by SSc was associated with development of ES (OR = 40.11, p = .0017). Patients with manifestation of sAD had a higher modified Rodnan skin score (mRSS) reduction after aHSCT (90.50% vs. 60.00%, p = .0064, r = .65). Thus, IAEs are common after aHSCT for SSc and can occur in different stages during and after aHSCT with characteristic clinical manifestations. Good cutaneous response after aHSCT might be considered as a risk factor for sAD, and higher age at aHSCT and cardiac involvement might be considered as risk factors for the development of ES.